2013
DOI: 10.1161/circulationaha.113.004122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Partner Bereavement on Quality of Cardiovascular Disease Management

Abstract: Background-Bereavement is a period of increased risk of cardiovascular death. There is limited understanding of the potential contribution of quality of cardiovascular disease management to this increased risk. Methods and Results-In a UK primary-care database, 12 722 older individuals with preexisting cardiovascular disease (coronary heart disease, hypertension, diabetes mellitus, stroke) and a partner bereavement were matched with a nonbereaved control group (n=33 911). We examined key routine annual process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Unfortunately, our analysis is underpowered to resolve whether this possible protection results from medication use, history of disease, or other unmeasured factors. However, we have recently shown that bereaved patients have poorer medication coverage before and immediately after bereavement, 32 so our findings may also reinforce the importance of adherence to a medication regimen in reducing the health impact of bereavement.…”
Section: Related Literaturesupporting
confidence: 71%
See 1 more Smart Citation
“…Unfortunately, our analysis is underpowered to resolve whether this possible protection results from medication use, history of disease, or other unmeasured factors. However, we have recently shown that bereaved patients have poorer medication coverage before and immediately after bereavement, 32 so our findings may also reinforce the importance of adherence to a medication regimen in reducing the health impact of bereavement.…”
Section: Related Literaturesupporting
confidence: 71%
“…We have previously shown that prescribing medication to lower lipid levels, antiplatelet medication, and drugs acting on the renin-angiotensin system fall in the immediate peribereavement period in patients at high risk of cardiovascular disease. 32 Longer-term behavioral changes affecting lifestyle factors, such as smoking and alcohol consumption, may also eventually contribute. 27 The absolute contribution of bereavement to overall cardiovascular event rates is likely to be small, because partner bereavement is usually a nonrepeated event for an indi-vidual, and the higher risk is relatively short-term.…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
“…A recent study found that individuals had fewer cardiovascular process of care measures (i.e. blood pressure, and cholesterol measures) and reduced medication refills in the year preceding spousal bereavement compared to matched controls (31); these results suggest diminished doctor and self-management of existing conditions in the year leading up to spousal bereavement and may explain why health deteriorations begin before bereavement. Although formal testing did not find evidence of new or worsening chronic conditions mediating the impact of bereavement on risk of death, it is possible that the health declines occur prior to bereavement (8).…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of the excess deaths due to cardiac 56 conditions in the early stages of bereavement may result from inadequate condition 57 management immediately prior to bereavement (Shah, Carey et al 2013), indicating that acute 58 stress at this stage contributes to the widowhood effect (Vable, Subramanian et al 2015). As 59 time since bereavement increases the mortality differential between widows and non-widows 60 tends to decrease for women in the first ten years but may increase subsequently, whereas men 61 are likely to show a sustained or increased mortality differential , 62 Berntsen, Kravdal 2012, .…”
mentioning
confidence: 99%